Progress of the Small Needle Knife Therapy Combined with Rehabilitation Technique for the Treatment of Shoulder-hand Syndrome (phaseⅠ) after Stroke - Zhao, Ya; Feng, Weixing (Journal of Contemporary Medical Practice, 2024)
To synthesize the relevant literature in recent years on the treatment of shoulder-hand syndrome (phaseⅠ) after stroke by small needle knife therapy combined with rehabilitation technology, and to organize the treatment plan of shoulder-hand syndrome (phaseⅠ) by small needle knife therapy combined with different rehabilitation technology, which is summarized from the aspects of PNF technology, exercise therapy, acupuncture, rehabilitation training, etc., so as to provide a more powerful basis for the selection of the plan for the treatment of shoulder-hand syndrome (phaseⅠ) after stroke by small needle knife therapy combined with rehabilitation technology in the future. The results were summarized from the aspects of PNF technique, exercise therapy, acupuncture, and rehabilitation training.